Extending the no objective testing rules to patients triaged by the ESC 0/1-hour algorithms. (3rd October 2022) - Boeddinghaus, J; Ratmann, P D; Nestelberger, T; Lopez-Ayala, P; Koechlin, L; Wildi, K; Miro, O; Martin-Sanchez, J; Christ, M; Gualandro, D; Rubini Gimenez, M; Keller, D; et al.
Abstract: Background: It is unclear which patients, after rule-out of non-ST elevation myocardial infarction (NSTEMI) with the European Society of Cardiology (ESC) 0/1h-algorithms, require further objective anatomical or functional cardiac testing and which do not. Purpose: To test the safety and efficacy of the no-objective-testing (NOT)-rules after NSTEMI rule-out by the well-validated ESC 0/1h-algorithms. Methods: We prospectively enrolled adult patients presenting with acute chest pain to 12 emergency departments (ED) in five European countries in an international, prospective, diagnostic multicenter study. The final diagnosis of major adverse cardiovascular events (MACE), defined as nonfatal acute coronary syndromes (NSTEMI or unstable angina) or cardiovascular death was centrally adjudicated by two independent cardiologists applying the 4th Universal Definition of myocardial infarction using all information including cardiac imaging and serial measurements of high-sensitivity cardiac troponin (hs-cTn) T/I. The primary endpoints were the safety and efficacy of the NOT-rules for the rule-out of MACE within 30-days follow-up including index events. Secondary endpoints included MACE within 365 and 730 days. Results: Among 4804 and 4569 eligible patients with available 0h and 1h hs-cTnT-Elecsys or hs-cTnI-Architect concentrations, 2783 (58%) and 2252 (49%) patients were eligible for application of the NOT-rules after rule-out of NSTEMI by the respective ESC hs-cTnT/I-0/1h-algorithm. The first rule (weighted score including age, sex, cardiovascular risk factors, previous MI or known coronary artery disease (CAD), nitrate use) identified 26% of patients, had a sensitivity of 100% (95% CI 98.3–100%), a negative predictive value (NPV) of 100% (95% CI, n.c.) for hs-cTnT-Elecsys and 99.4% (95% CI 96.7–99.9%) and 99.8% (95% CI 98.8–99.9%) for hs-cTnI-Architect, respectively. The dichotomized second (age <50y, no previous MI or known CAD, <3 risk factors, no nitrate use) and even simpler third rule (nitrate use omitted) both identified 31% of patients with 99.5% (95% CI 97.4–99.9%) sensitivity and a NPV of 99.9% (95% CI 99.2–99.9%) for hs-cTnT-Elecsys. Sensitivities were 98.8% (95% CI 95.7–99.9%) and NPV 99.7% (95% CI 98.9–99.9%) for hs-cTnI-Architect. High safety was confirmed with consistently very high sensitivities and NPV for 365-day and 2-year MACE. Conclusion: All three NOT-rules performed very well for rule-out of MACE. The third NOT-rule best balanced feasibility, safety and efficacy by identifying nearly one out of three patients as low-risk, who may not require further cardiac testing. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Swiss Heart Foundation, University of Basel.